Новый иммунохимический диагностикум для выявления опасных инфекций на основе ультрадисперсных алмазов детонационного синтеза - Шугалей, И.В.; Тофтунова, В.В.; Дубяго, Н.П.; Гусейнова, В.В.; Иванова, А.А.; Иванов, А.М.; Долматов, В.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Ultradisperse diamonds of detonation synthesis (NDs) being possible firmly to adsorb specific antigenes on the surface of the grain were chosen as the basic core of immunochemical diagnosticum. It was shown that only specially treated sample of NDs – TAN does not agglomerate in physiological conditions. One of the first constructed diagnosticums of such type is the test-system for exposing syphilis infection. Several antigenes of Treponema pallidium being the pathogenic organism and provoking syphilis infection in humans were tested for binding with NDs particles. The protein antigene with M = 41000 was chosen as the preferable one. The complex of NDs with this antigene is the base of the created diagnosticum. Currently the composition of the diagnosticum has been optimized, the ratio of NDs:antigene has been chosen and the reaction conditions have been selected. The constructed diagnosticum is stable for 30 days. It shows high sensivity (95 %). The diagnosticum also displays very high specificity (up to 100 %).